IMPORTANCE OF QTC INTERVAL DURATION IN PACING PARAMETERS OPTIMIZATION AND THERAPEUTIC MANAGEMENT OF THE PATIENTS WITH PERMANENT CARDIAC PACING - MaltsevaМ. S.; Volkov, D. E. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
Clinical importance of QT interval duration in patients with permanent pacemakers (PM) is discussed in the review. Physiological interpretation, methods of heart rate frequency normalization, changes under PM and role of pacing optimization parameters, reactions on medications in patients with spontaneous and stimulated rhythm, meaning for life quality and survivability of patients with permanent PM are considered.